Randomized sham‐controlled trial evaluating efficacy and safety of endoscopic gastric plication for primary obesity: The ESSENTIAL trial. Issue 2 (21st December 2016) - Sullivan, Shelby; Swain, James M.; Woodman, George; Antonetti, Marc; De La Cruz‐Muñoz, Nestor; Jonnalagadda, Sreeni S.; Ujiki, Michael; Ikramuddin, Sayeed; Ponce, Jaime; Ryou, Marvin; Reynoso, Jason; Chhabra, Rajiv; et al.
Abstract : Objective: Evaluate safety and efficacy of the pose™ procedure for obesity treatment. Methods: Subjects with Class I to II obesity were randomized (2:1) to receive active or sham procedure, after each investigator performed unblinded lead‐in cases. All subjects were provided low‐intensity lifestyle therapy. Efficacy end points were the mean difference in percent total body weight loss (%TBWL) at 12 months between randomized groups, and responder rate achieving ≥5% TBWL. The primary safety end point was incidence of reported adverse events. Results: Three hundred thirty‐two subjects were randomized (active, n = 221; sham, n = 111); thirty‐four subjects were included in the unblinded lead‐in cohort. Twelve‐month results were mean TBWL 7.0 ± 7.4% in lead‐in, 4.95 ± 7.04% in active, and 1.38 ± 5.58% in sham groups, respectively. Responder rate was 41.55% in active and 22.11% in sham groups, respectively ( P < 0.0001); mean responder result was 11.5% TBWL. The differences observed between active and sham groups for co‐primary end points were statistically significant ( P < 0.0001); however, super superiority margin as set forth in the study design was not met. No unanticipated adverse events or deaths occurred. Procedure‐related serious adverse event rates were 5.0% (active) and 0.9% (sham), P = 0.068. Conclusions: The pose procedure was safe and resulted in statistically significant and clinically meaningful weight loss over sham through 1 year.